TRANSPARENCY IN THE PROVINCIAL COMPETITIVENESS INDEX THE CASE OF VINH LONG PROVINCE, VIETNAM - Cao Thanh, Phong (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
The Provincial Competitiveness Index is increasingly being studied in scholarly articles. In 2021, the index was completed and added new indicators to increase the overview, compre hensiveness, and support of the state apparatus in the provinces and cities in public administration and investment attraction. Using the Provincial Competitiveness Index 2021 Report, the authors have made statistics and analyzed the competitiveness indicators of Vinh Long Province. With theoretical synthesis and analysis of secondary data, the study concentrates on transparency indicators, aiming to detect the positive aspects as the limitations of the province in the context of comparison in the Mekong Delta. Through the results, the authors have proposed the UTAUT2 model to create a theoretical framework to increase the participation and use of electronic information in the business community, which improves PCI and determines the direction of public administration in the coming time.